Assessing the Impacts of Manure Timing and Innovative Cover Cropping Techniques on Crop Yield and Drainage Water Quality - Gabrielle Myers; Daniel S Andersen; D.Raj Raman; Kenneth J Moore; Kenneth Pecinovsky; Carl H Pederson; Matthew J Helmers (Hello World!, 2024)
This study aims to evaluate the impact of manure application timing and different cover cropping strategies on drainage water quality and crop yields. Treatment comparisons asses the effects of fall vs. spring-injected liquid swine manure, spring urea ammonium-nitrate (UAN) sidedress, and three different treatments with either annual or perennial cover crops. This information can be used to develop appropriate manure and cover crop practices to minimize nutrient loss and enhance the use of swine manure as nutrient resource.